Learning Strategy for Lecturers of PAI UIN Ar-Raniry Banda Aceh During the Covid-19 Period - Mardhiah, Ainal (Pascasarjana Universitas KH. Abdul Chalim, 2023)
Under normal conditions, learning is carried out directly face-to-face. During the Covid-19 pandemic, learning is online via the internet network. Online learning during the Covid-19 era was something new, experiencing various obstacles and problems. This research aims to determine the planning, constraints, and efforts to implement learning in the PAI Study Program UIN Ar-Raniry Banda Aceh during the Covid-19 period. The methodology that the writer uses is field research and laboratory research. The research results can be concluded that PAI lecturers' learning planning during the Covid 19 period was by making an RPS (Semester Learning Plan) form. The obstacles faced are constraints on the ability of lecturers to master digital media or IT and internet network regulations that are difficult or often not good so that learning sometimes cannot be carried out. Problems with laptop facilities, mobile phones need more capacity and facilities. The campus's online learning facilities or systems at the start of Covid 19 were sometimes problematic due to economic constraints for delivering data or internet packages. For internet network problems, lecturers look for internet networks on campus, in cafes, or with hotspots. For obstacles to mastery of applications and learning strategies, lecturers try to seriously learn on online learning applications or platforms by independently or taking part in training made by the campus and asking colleagues.